A vida humana cmo pressuposto da cidadania - Castro, Pierre Santos (2007)
In Brazil, we are around 170.000.000 Brazilians. A number about 3% of Brazilian population would get benefits with researches involving stem cells, as science promises. In this work we deal with life of 5.000.000 people without measuring the number of unborn which are in labs. The law that treats Brazilian biosecurity is law 11.105/05, however this law assails constitutional laws. Considering the Magna Carta the maxim law in our nation, this work treats the inconstitutionabilty of this biosecurity law cause by some aspects like using embryos as human cavies to foment researches as it says the article 5º of the law 11.105/05, which assails the constitutional right to life inserted at this article of the C.F. Keeping human lives in labs, considering that the surplus embryos are frozen, attacks the dignity of human beings, as it says the article 1º inc. III C.F and rejecting embryos which are frozen for more than three years is also figured an attempt against life and dignity of the human being, article 1º inc. III C.F. We argue the researches with stem cells: cells of embryos which presents the capability of overcoming in cell of any tissue of the organism, as we believe that it would be necessary to sacrifice the human embryos concepted in vitro and it takes us to a legal and ethic issue. The ethic values important to legal protection were discussed in the promulgation of Federal Constitution in 1998. Such values of human life are clausulas petreas of our Magna Carta and in order to revise these questions, only a new constitution would be able to. While developing this work, we will analyze the foreign law, the scientific, philosophical and religious values that figurate the ethic values inserted in legislation and which in a great number defend life, the human being and the fraternity between humans, as well the scientific theories as the Conception Theory, Nidaton Theory, Formation Theory of rudiments and juridical laws as the Natality Theory, Conditional Theory and Conceptions Theory.